The Acceptance of Treatment among Breast Cancer Patients and its Relations with Some Variables - Field study at Tishreen University Hospital “Department of Cancer Oncology” in Lattakia City - Yousof, Rania Ali (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
The research aimed to know the Extent of the Treatment Acceptance among Breast Cancer Patients at Tishreen University Hospital “Department of Cancer Oncology” in Lattakia City, also aimed to examine the differences in Treatment Acceptance(Social status, duration of the disease, age, education level). The research used Descriptive analytical method, The sample included (118) breast cancer patients in the year 2019. And to take the questionnaire President to measuring Treatment Acceptance from the views of sample. Validity of the questionnaire was established though a jury of (7) of the teaching staff. Pilot sample consisted of (24) breast cancer patients. Reliability was established by Cronbach – Alpha Reliability (0.861), also the Spearman-Brown which reach (0.883). The research ended up with the following results: - The Extent of the Treatment Acceptance among Breast Cancer Patients at Tishreen University Hospital “Department of Cancer Oncology” in Lattakia City was in medium degree. - No statistically significant differences regarding the Extent of the Treatment Acceptance according to the variable duration of the disease. - There are statistically significant differences regarding the Extent of the Treatment Acceptance according to the variable age in favor of the more than (40) years, and according to the variable Social status in favor of the marries, also according to the variable education level in favor of the licentiate. هدف البحث إلى تعرُّف درجة تقبل العلاج لدى مريضات سرطان الثدي في مشفى تشرين الجامعي (قسم الأورام السرطانية) في مدينة اللاذقية، والكشف عن الفروق بين إجابات أفراد عينة البحث من مريضات سرطان الثدي في درجة تقبل العلاج تبعاً للمتغيرات الآتية (الحالة الاجتماعية، مدة الاصابة بالمرض، العمر، المستوى التعليمي). استخدم المنهج الوصفي، واشتملت عينة البحث على (118) مريضة سرطان الثدي في مدينة اللاذقية لعام 2019، واتخذت الباحثة من الاستبانة أداةً رئيسة لقياس تقبل العلاج لدى أفراد عيّنة البحث، وللحكم على صدق الاستبانة عرضت على مجموعة مؤلفة من (7) محكمين مختصين، وتم التأكد من ثباتها بتطبيقها على عينة استطلاعية شملت (24) مريضة سرطان الثدي من خلال حساب معامل ألفا كرونباخ (Cronbach – Alpha)، والذي بلغ (0.861)، وكذلك من خلال حساب معامل سبيرمان براون (Spearman-Brown) الذي بلغ (0.883). توصلت نتائج البحث إلى الآتي: - إن مدى تقبل العلاج لدى مريضات سرطان الثدي في مشفى تشرين الجامعي في مدينة اللاذقية جاءت بدرجة متوسطة. - عدم وجود فروق ذات دلالة إحصائية في درجة تقبل العلاج لدى مريضات سرطان الثدي تبعاً لمتغير مدة الاصابة بالمرض. - وجود فروق ذات دلالة إحصائية في درجة تقبل العلاج تبعاً لمتغير العمر لصالح ذوات الأعمار (40) فأكثر، وتبعاً لمتغير الحالة الاجتماعية لصالح المتزوجات، وتبعاً لمتغير المستوى التعليمي لصالح المريضات من حملة الإجازة الجامعية.